PESANTREN DAN PENDIDIKAN TINGGI - M Sahibudin, M Sahibudin (Universitas Islam Madura, 2017)
Pesantren is the center of Islamic education in Indonesia, where the students are studying. The word santri itself is used to find on the group of Muslims in Java who have a stronger tendency on the teachings of his religion, some say that this pesantren education is the original Indonesian tradition, so this boarding school education is a feature that has Indonesia. In a boarding school of course there are a lot of elements that are interconnected and very related existence of one with the other. Like kiai, asatidh (the teachers), as well as the santri (as learners) as well as the existence of classical books (yellow book) and so on. Education Pesantren and yellow book it is a very sustainable and is the development of Islamic scholarship tradition, especially in Indonesia. Several streams later emerged as modernists, reformers and fundamintalis. In addition, the upgrading of pesantren educational institutions is not only limited to formal religious education alone, but also has established universities in the form of high schools, institutes and even universities. The synergy of the pesantren and college educational institutions becomes a dance of attention when the two institutions are complementary to one another.